Analysis of self confidence levels in roller skating athletes - Suryawati Suryawati; Rizki Burstiando Rizki Burstiando; Wasis Himawanto; Budiman Agung Pratama (Universitas Sriwijaya, 2022)
This study aims to analyze the level of self-confidence of athletes at the FIST roller skating club in Tulungagung, with a sample of 13 athletes. The method used in this research is descriptive quantitative non-experimental. The instrument in this study is a closed questionnaire and the scale used is the Likert scale and obtains data from a questionnaire that has been distributed to the sample. The results showed that the self-confidence level of FIST roller skate athletes in Tulungagung was based on 2 factors that influenced the level of self-confidence, namely, external factors obtained the